Refugee law : with case laws & materials - Rashid, Harun ur, 1934- (Dhaka : Anupam Gyan Bhandar, 2000)
On basic issues of refugees under international law and the position of Bangladesh on the issues of refugees.
Keywords: Refugees -- Legal status, laws, etc. -- Bangladesh; Refugees -- Legal status, laws, etc. -- Digests